2018
DOI: 10.1038/s41467-018-04799-0
|View full text |Cite
|
Sign up to set email alerts
|

Strong lowering of ionization energy of metallic clusters by organic ligands without changing shell filling

Abstract: Alkali atoms have unusually low ionization energies because their electronic structures have an excess electron beyond that of a filled electronic shell. Quantum states in metallic clusters are grouped into shells similar to those in atoms, and clusters with an excess electron beyond a closed electronic may also exhibit alkali character. This approach based on shell-filling is the way alkali species are formed as explained by the periodic table. We demonstrate that the ionization energy of metallic clusters wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 37 publications
3
33
1
Order By: Relevance
“…An additional phenomenon combines with the traditional ligand field effect to explain the changes in AEA and VDE: PEt 3 and CO form charge transfer complexes, and the induced dipoles at the cluster surface play a critical role in changing the electronic properties. As a reference, surface dipoles can either increase or decrease the work function of metals 47,48. In this case, as PEt 3 ligands are replaced by CO, the sign of the dipole changes and hence AEA increases as more CO are bound to the core.…”
Section: Resultsmentioning
confidence: 99%
“…An additional phenomenon combines with the traditional ligand field effect to explain the changes in AEA and VDE: PEt 3 and CO form charge transfer complexes, and the induced dipoles at the cluster surface play a critical role in changing the electronic properties. As a reference, surface dipoles can either increase or decrease the work function of metals 47,48. In this case, as PEt 3 ligands are replaced by CO, the sign of the dipole changes and hence AEA increases as more CO are bound to the core.…”
Section: Resultsmentioning
confidence: 99%
“…14,15,25,26 The location of the Fermi energy in such systems can be controlled by changing the ligands providing the ability to control the band gap energy using the same metallic core. 22,23 We also show that superatoms acquire a spin magnetic moment for partial coverage with ligands offering potential for creating magnetic semiconductors unless the metal core can relax through a Jahn-Teller distortion. 27,28 The properties of these semiconductors with supported superatomic clusters can be understood by considering the surface as a ligand that stabilizes a superatomic cluster.…”
Section: Introductionmentioning
confidence: 73%
“…We have found that this can be accomplished by attaching ligands that form charge transfer complexes. 22,23 In such ligated species, every time an electron is withdrawn, the crystal field generated by the ligands pushes up the electron manifold and in particular the highest occupied molecular orbital (HOMO), thus reducing the cost for withdrawing the subsequent electron. The effect, which is especially prominent in charge donating ligands such as phosphines is so powerful that the energy reduction can be several electron volts.…”
Section: Introductionmentioning
confidence: 99%
“…By the same token, they successfully designed another alkali‐like superatom Co 6 Te 8 (PEt 3 ) 6 with a closed electronic shell and a low ionization energy of 4.74 eV . More recently, they demonstrated that the ionization energy of metallic clusters can be dramatically lowered by attaching organic ligands . These findings are indeed surprising as the ligands of conventional superalkalis consists of alkali metal atoms that can easily release their electron, whereas in these complexes the central cores are surrounded by organic molecules.…”
Section: Theoretical Design Of Superalkalismentioning
confidence: 99%